The term structure of interest rates - Nelson, Charles R. (New York : Basic Books, 1972)
The book adopted an expectational approach to explain yield differentials among fixed-interest securities of different maturities.
Includes bibliographical references: p. 121-123.
ucj, 15/01/2019
Loans
Keywords: Interest rates